Tinjauan Kriminologi Terhadap Premanisme Parkir Liar (Studi Kota Pekanbaru) - Askarial; Bowo, Probowo Yusgiantoro (Sisi Lain Realita, 2024)
Pekanbaru City has currently developed into a city that has quite high community mobility, this can be seen from the high level of vehicle mobility. This also causes other problems, namely the availability of parking lots and their management, so that this often leads to acts of illegal parking thuggery. The purpose of this research is to find out how the criminological review of acts of thuggery, carried out using qualitative methods and a descriptive approach, results in research that acts of thuggery are related to the presence of illegal parking individuals who carry out parking activities using acts of violence and intimidation. As well as setting prices that are not in accordance with existing regulations. Then, after an analysis was carried out using rational choice theory, it was clear that what caused this act of illegal parking thuggery was because this business was rationally profitable and several economic concepts were applied along with calculations by each of the perpetrators which caused unrest among the people who used parking services.